2019
DOI: 10.4103/sajc.sajc_389_18
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogression after immunotherapy

Abstract: Introduction:Checkpoint inhibitors demonstrate very good anticancer effects, and some patients are long-time responders. As our experience to use these drugs increases, we see more and more patients having different kind of side effects which are usually not seen with chemotherapy. We have observed a subset of patients who appear to be “hyper-progressors,” with a greatly accelerated rate of tumor growth and clinical deterioration compared to pretherapy, which was also recently reported by Institut Gustave Rous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“… 24 Ten studies included various types of cancer, which limited tumor type–based subgroup analysis. 5 , 8 , 11 , 12 , 14 , 17 , 18 , 25 , 26 , 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 Ten studies included various types of cancer, which limited tumor type–based subgroup analysis. 5 , 8 , 11 , 12 , 14 , 17 , 18 , 25 , 26 , 28 …”
Section: Resultsmentioning
confidence: 99%
“…independently selected literature eligible for review. Disagreements between the 2 reviewers occurred regarding 2 studies 27 , 28 and were resolved by consensus with 1 of us (S.Y.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TNM stage or T stage was not significantly related to HPD development in this study, this was attributed to the advanced disease stages (stage IV and T4) of all HPD patients enrolled in this study. Conversely, several studies have reported no significant association between other markers of tumor burden (sum of the largest diameter of target lesions at baseline, tumor volume at baseline on volumetric measurement) and HPD development 13, 17, 18 . However, these studies had different definitions of HPD and inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several studies have reported no significant association between other markers of tumor burden (sum of the largest diameter of target lesions at baseline, tumor volume at baseline on volumetric measurement) and HPD development. 13,17,18 However, these studies had different definitions of HPD and inclusion criteria. Therefore, multicenter studies with a consistent design are warranted.…”
Section: Discussionmentioning
confidence: 99%